Analisis Pengendalian Kualitas Produk Tahu Menggunakan Metode Seven Tools Pada UMKM Tahu Bu Ida - Ide Muhammad Hakim; Kevin Seviano Tangseng; Martinus Wisnu Saputra; Ari Zaki Al-Faritsy (Manufaktur: Publikasi Sub Rumpun Ilmu Keteknikan Industri, 2024)
MSME Tofu Bu Ida is a processed tofu business located in Sengkan RT 07 RW 59 Njoho Depok, Sleman. Along with the development of MSME Tofu Bu Ida, which has long started a business since 1980, it turns out that these MSME are still found errors and product defects in every production process. The general problem in MSME Tofu Bu Ida is that there are defective production results and an undisciplined workforce. These problems certainly interfere with the production process and partially inhibit and reduce product quality. This research produces data containing several types of tofu damage accompanied by the amount of damage and corrective steps that can be taken to overcome the problem.The results of the analysis show that there is a lot of damage that occurs during the production process, therefore it is necessary to provide repairs to prevent damage from continuing. Improvement steps that can be taken are using a tofu cutter, using a press, increasing lighting, and establishing SOP.